An efficient cooperative routing algorithm for large-scale wireless networks based on capacity and location. (27th April 2021) - Kumar, D. Praveen; Saradhi, P. Pardha
Cooperative communication has been extensively used in small-scale wireless networks, by virtue of its capability to mitigate the fading effects. Extending cooperative communication technique to large-scale networks undergoes severe interference; multi-radio-multi-channel is exploited in large scale wireless networks to ameliorate throughput by concurrent transmissions over orthogonal channels to dwindle interference. Capitalising on these potential advantages, stand in need for efficacious routing and potent mapping of channels to radios. In this paper, we have proffered an algorithm by concurrently considering: 1) relay selection using distance and maximum-available-channel-capacity parameters; 2) channel assignment using dynamic global table. Our algorithm selects a relay-node based on the available channel capacity in the shortest-path to minimise the transmission delay without affecting aggregate throughput. The evaluation and analysis of the proposed model is compared with interference-aware-cooperative-routing algorithm and observed that the proposed algorithm has improved delay reduction by 27.5% and the average number of hops by 32.5%.